EFFECTS OF CONSTRUAL LEVELS AND SELF-CONTROL STRENGTH IN EFFORTFUL CYCLING EXERCISE - Tran, Alex (My University, 2013)
Self control is affected by self-regulatory strength depletion (Hagger et al., 2010) as well as construal-level mindset (Fujita et al., 2006). However, two conflicting perspectives have emerged predicting differential interactive effects of construals and depletion. The purpose of the present study was to investigate the independent and interactive effects of construal levels and self-control strength in an effortful cycling exercise task. Using a randomized 2 X 2 factorial design, undergraduate participants (N = 67, n = 34 women) completed a baseline cycling task, followed by a self-control depletion manipulation (Stroop task vs. quiet rest; Wallace & Baumeister, 2002), a construal-level manipulation (category vs. exemplar naming task; Fujita et al., 2006), and then a 10-minute strenuous cycling test trial. The results showed no main effects for either self-control strength depletion or construal level (p > .20). However there was a near-significant interaction effect (p = .07) indicating the depleted group outperformed the non-depleted group in the low-construal condition, whereas the opposite effect occurred in the high-construal condition. The results provide novel insights of the effects of self-control strength depletion and construal mindsets on exercise performance and implications for the design of construal level and self-control depletion research.
Keywords: self regulation; self control; construal level theory; exercise; endurance cycling; Psychology of Movement; Psychology of Movement